Does daily co-administration of letrozole and gonadotropins during ovarian stimulation improve IVF outcome? - Jigal Haas; Rawad Bassil; Jim Meriano; Nivin Samara; Eran Barzilay; Noa Gonen; Robert F. Casper (BMC, 2017)
Abstract Background For the last year we have been treating normal responders with gonadotropins and letrozole during the whole stimulation in order to improve response to FSH by increasing the intrafollicular androgen concentration, and to reduce circulating estrogen concentrations. The aim of this study was to compare the IVF outcome of normal responders treated with letrozole and gonadotropins during ovarian stimulation with patients treated with gonadotropins only. Methods A single centre retrospective cohort study of 174 patients (87 in each group). Results The age of the patients was comparable between the groups. Estradiol levels were significantly higher in the control group (6760 pmol/L vs. 2420 pmol/L respectively, p < 0.01), and the number of follicles ≥15 mm at the trigger day was significantly lower in the control group (7.9 vs. 10, p = 0.02). The number of retrieved oocytes (10 vs. 14.5, p < 0.01), MII oocytes (7.9 vs. 11.2, p < 0.01) and blastocysts (2.7 vs. 4.0, p = 0.02) was significantly higher in the study group. We found no significant differences in the cumulative pregnancy outcome between the two groups (65.2% vs 58.3% p = NS). Conclusions We conclude that co-treatment with letrozole improves the IVF outcome in normal responders in terms of increased number of blastocysts obtained without increasing the pregnancy rate or the risk of OHSS.